THE WHITE’S FELONY IN FIVE POEMS BY BENJAMIN ZEPHANIAH - Fitri Handayani; Kurnia Ningsih; Desvalini Anwar (English Language and Literature, 2018)
This study is aimed to expose the issue about the White’s felony which is done by the white people toward the Black and to know the contribution of poetic elements; imagery, irony and repetition in revealing the issue of the White’s felony. This analysis is related to the concept of Otherness by Edward Said in post-colonial approach. The result of this analysis shows that the White’s felonies are done by the policemen, parliament members and societies.